Clustering, connectivity and hierarchies in the internet global supply chain networks - Alessio D'Ignazio; Emanuele Giovannetti (International Telecommunications Society (ITS), 2012)
Internet Service Providers compete for customers while exchanging traffic flows to provide a complete, end to end, service to final users. This requires reliable interconnections among competitors that form multiple Global Supply Chain Networks (GSCNs) for the delivery and exchange of Internet traffic. Interconnection decisions form the architecture of the Internet supply chain as they design the rules of the game played by the operators, in terms of reciprocal access pricing and quality and modalities of traffic exchanged. From a provider's point of view, the strategic assessment of its direct interconnection environment is crucial in defining the competitive and complementary elements of its extended GSCN. This paper focuses on the relationship between a provider's connectivity and the degree of mutual connectivity among the operators this provider is connected to.The strategic relevance of this relationship is clearly explained as follows: thebetter connected a provider is, the easier it is to deliver its traffic with high Quality of Service and low costs, while the less interconnected among themselves a provider's neighbours are, the easier it is, for the provider, to exert its bargaining power over them. This bargaining power, of a wellconnected provider over its poorly connected network - neighbours, shows when contracting over quality standards, access pricing and interconnection terms. This paper estimates two separate econometric models showing that the connectivity features of the GSCN display significant differences in network hierarchy and complexity depending on whether they are observed from a European, North American or Rest of the World observation point.
Keywords: 330; Internet; Complexity; Global Supply Chain Networks; Clustering; Connectivity